2016
DOI: 10.4172/2161-0673.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Doping Knowledge and Opinions of South African Pharmacists and General Practitioners

Abstract: Objective: Despite the prevalence of doping in sport and the need for doping prevention strategies, information about doping awareness among medical professionals is limited. The aim of this pilot study was to investigate the knowledge and attitude of South African pharmacists (Ps) and general practitioners (GPs) towards doping in sports.Methods: An online survey questionnaire was completed by 98 Ps and 201 GPs the questionnaire incorporated a range of questions that probed the participant's knowledge and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The paucity of doping knowledge in these aspects limits the Kenya General Practitioners' competence in treating athletes in compliance with WADA requirements. Similar findings were reported among Serbian general practitioners, and medical practitioners from the Balkan region (Bulgaria, Greece, Romania, Serbia, and Turkey), and South African general practitioners, where low doping knowledge was linked to a lack of doping topics in college, lack of interests in doping, and insufficient training (Dikic et al, 2008;Antic, 2017;Dorota & Derman, 2016;Starzak et al, 2021). In sports, low and even average doping knowledge incapacitates General Practitioners' ability to treat competitive athletes in line with antidoping agencies' requirements and effectively contribute to the fight against doping.…”
Section: Discussionsupporting
confidence: 68%
“…The paucity of doping knowledge in these aspects limits the Kenya General Practitioners' competence in treating athletes in compliance with WADA requirements. Similar findings were reported among Serbian general practitioners, and medical practitioners from the Balkan region (Bulgaria, Greece, Romania, Serbia, and Turkey), and South African general practitioners, where low doping knowledge was linked to a lack of doping topics in college, lack of interests in doping, and insufficient training (Dikic et al, 2008;Antic, 2017;Dorota & Derman, 2016;Starzak et al, 2021). In sports, low and even average doping knowledge incapacitates General Practitioners' ability to treat competitive athletes in line with antidoping agencies' requirements and effectively contribute to the fight against doping.…”
Section: Discussionsupporting
confidence: 68%
“…However, doping substances are not covered in a separate chapter titled "Doping." Doping in sports is not covered in undergraduate pharmacy curricula [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data collectors were trained for two days on how to introduce study tools to the study participants and check the completeness of the collected questionnaire. The questionnaire was developed after an extensive literature review on knowledge (K), attitude (A), and practice (P) of the pharmacy profession towards doping [ 17 , 18 , [24] , [25] , [26] , [27] ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that, although some pharmacists express a desire to learn more about this specialty, they lack doping-related knowledge, and are not adequately trained to practice sports pharmacy. 24,25 Studies have also suggested that educational programs relating to sports pharmacy could be developed and implemented into pharmacy curricula and continued education programs. 22,26 Interestingly, some participants believed the role of the pharmacist was limited only to dispensing medications.…”
Section: Discussionmentioning
confidence: 99%